Development of Students Worksheet based on Realistic Mathematics Education in Indonesia - Maulana, Monif; man, Supar (International Journal of Engineering and Technology, 2018)
A concept of mathematics is one of the essential goals in learning mathematics. Providing an understanding that the material taught to students is not only as a recitation but also as the concept of the subject matter itself. This study aims to develop student worksheet based on realistic mathematical approach. The method used in this study is the stages of 4-D development research which consists of defining, designing, developing, and disseminating. This study employed two data collection instruments. The first is expert validation which was used to measure the validity. Meanwhile the second is questionnaire which was used to measure students’ practicality and to get product development assessment from experts and students. The results showed that the developed worksheet is valid with the validity level of 3.67 for the content aspect, 3.60 for the constructed aspect, and 3.50 for the language aspect. The worksheet was tested to 21 students of grade VII in MTs N 2 Gunungkidul Indonesia. The test results stated that the worksheet received a good response from students. Therefore, it can be used in the process of learning mathematics in class.